Analisis Kerusakan Wire Rope (Tali Baja) Pada Hoist Crane 5 Ton Menggunakan Metode Plan Do Check Action (PDCA) Studi Kasus Pada Perusahaan Manufaktur - Anang Wahyudi; Fibi Eko Putra; Heru Darmawan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Along with the rapid development of the era, manufacturing companies are facing more challenges and demands to increase efficiency in the production process. Regular maintenance of production facilities is a major factor in supporting company productivity. One of the important equipment in supporting large-scale manufacturing is the use of heavy equipment, such as hoist cranes, to facilitate the process of lifting and moving materials. However, one of the problems that often occurs is damage to important components, such as wire ropes, which can hamper operations and cause significant downtime. This study aims to analyze the causes of wire rope damage to a 5-ton hoist crane in a manufacturing company. Through the Total Productive Maintenance approach carried out using the Fishbone Diagram and 5W + 1H methods, the root cause of the damage that occurs can be identified. This study found that wire rope damage was caused by several factors, namely there were gaps in the eroded panel walls, frequent friction between the wire rope and the panel wall, no safety when the wire rope was piled up, and there were no clear work instructions for operating the hoist crane. The results of the improvement implementation showed significant improvements. The downtime of the hoist crane unit was successfully reduced from 596 hours 50 minutes in February 2023 to only 12 hours 55 minutes in March 2023, and further to only 2 hours 30 minutes in April 2023. In addition, the improvements also succeeded in increasing the Physical Availability of the hoist crane, from 69.3% in February 2023 to 96.4% in March 2023, and 98.8% in April 2023